The COMmons Places ASSessment (COMPASS) Framework for the Governance of Common Goods: A Comparison of Evolving Practices - Maria Cerreta; Fabrizia Cesarano; Stefano Cuntò; Laura Di Tommaso; Ludovica La Rocca; Caterina Loffredo; Sveva Ventre; Piero Zizzania (Land)
In recent years, the concept of the commons has gained relevance across academic, legal and civic spheres as an alternative framework for managing shared resources. Rooted in Elinor Ostrom’s seminal work on collective governance, contemporary debates on the commons increasingly challenge the traditional binary of private versus public ownership by foregrounding the social function of these resources and the role of their communities in their administration. Urban commons, in particular, have emerged as dynamic spaces of experimentation, where local actors reclaim underutilised or abandoned assets and activate them through bottom-up processes of care, cultural production, and civic innovation. While international literature provides a robust conceptual foundation for understanding commoning practices, their practical implementation mostly depends on local specificities, such as legal and social contexts. Despite the important milestone of the Rodotà Commission’s proposal (2007) and Law 168/2017 on collective domains, the Italian regulatory framework remains highly fragmented, with regional and municipal regulations pioneering policies and practices frequently driven by community-led efforts to redefine the use and governance of public assets. This paper contributes to the growing debate on urban commons by investigating how, since 2011, experiences of collaborative care of the commons in Southern Italy have rekindled interest in the issue raised in 2007, highlighting a strong connection between the regulatory and social dimensions of these processes. The study develops a methodological framework—the COMmons Places ASSessment (COMPASS)—to evaluate the enabling conditions and governance dynamics of these processes. The research specifically focuses on five case studies in the Campania region, where diverse actors have mobilised to reclaim and transform public heritage through cultural, social, and creative activities. From the results, insights on collective management practices emerge potentials and criticalities of the analysed governance, as well as of the designed decision-making process and their effectiveness for the open, participatory, and sustainable management of urban commons.